The Routledge Handbook of Digital Sport Management. - Naraine, Michael L., 1987-; Hayduk, Ted.; Doyle, Jason P. (Abingdon, Oxon ; New York, NY : Routledge, 2023)
The Routledge Handbook of Digital Sport Management provides students, researchers, and practitioners with a contemporary roadmap of the impact of digital technologies in sport management, at all levels and in all sectors, in a global context. Divided into three sections addressing digital transformations, digital tools, and emerging digital issues, this book explores the impact of digital technology in the core functional areas of sport management, such as sponsorship, event management, and human resources. It introduces essential digital innovations such as esports, social media, VR, wearables, analytics, and artificial intelligence, and examines the debates and issues that are likely to shape and transform sport business over the next decade. The only book to survey the full sweep of digital sport management, this book is an essential reference for all serious students of sport business and management, any researcher working in the nexus of sport business and digital, and all managers, policy-makers or associated professionals working in the sport industry.
Digital Technology in Organizations -- Digital Transformation in Organizations -- Organizational Strategy -- Organizational Structure and Design -- Leadership and Human Resources -- Emerging Trends -- Conclusions and Future Research Directions -- References -- 6. Virtual Participatory Sport Events -- Introduction -- Participatory Sport Events -- Digital Disruption of the Participatory Sport Event Market -- Social Leveraging of Participatory Sport Events -- Fostering Social Interaction -- Prompting a Sense of Celebration -- Social Leveraging and Virtual Running Events
Social Leveraging Through Participants' Experiences of Virtual Running Events
Keywords: Sports administration -- Technological innovations; Sports -- Marketing -- Technological innovations; Hosting of sporting events -- Technological innovations; Sports -- Technological innovations; BUSINESS & ECONOMICS / E-Commerce / General (see also COMPUTERS / Electronic Commerce); SPORTS & RECREATION / General